2004
DOI: 10.1073/pnas.0407262101
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid hormone administration enhances remyelination in chronic demyelinating inflammatory disease

Abstract: Chronic disabilities in multiple sclerosis are believed to be due to neuron damage and degeneration, which follow remyelination failure. Due to the presence of numerous oligodendrocyte precursors inside demyelination plaques, one reason for demyelination failure could be the inability of oligodendrocyte precursor cells to turn into myelinating oligodendrocytes. In this study, we show that thyroid hormone enhances and accelerates remyelination in an experimental model of chronic demyelination, i.e., experimenta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
101
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 126 publications
(110 citation statements)
references
References 69 publications
5
101
0
Order By: Relevance
“…TTR is a component of the network determining thyroid hormone (TH) distribution (Fernandez et al, 2004). It is well established that TH is required for the normal timing of differentiation and maturation of oligodendrocyte precursor cells (OPCs), the most important source of remyelinating oligodendrocytes in the adult CNS (Fernandez et al, 2004). OPCs are present in early (fresh) demyelinating lesions in MS were they fail to differentiate (Fernandez et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…TTR is a component of the network determining thyroid hormone (TH) distribution (Fernandez et al, 2004). It is well established that TH is required for the normal timing of differentiation and maturation of oligodendrocyte precursor cells (OPCs), the most important source of remyelinating oligodendrocytes in the adult CNS (Fernandez et al, 2004). OPCs are present in early (fresh) demyelinating lesions in MS were they fail to differentiate (Fernandez et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
“…During ontogeny, the maximum TTR synthesis in the choroid plexus precedes that of the growth rate of the brain and occurs during the period of maximum neuroblast replication. TTR is a component of the network determining thyroid hormone (TH) distribution (Fernandez et al, 2004). It is well established that TH is required for the normal timing of differentiation and maturation of oligodendrocyte precursor cells (OPCs), the most important source of remyelinating oligodendrocytes in the adult CNS (Fernandez et al, 2004).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Possible pathogenetic mechanisms for neuronal damage such as neuroprotective strategies are under active investigation also in experimental allergic encephalomyelitis (EAE), the most widely used experimental model for MS. We recently demonstrated that long-lasting neurological disabilities in EAE correlates with neurochemical phenotype changes in spinal motoneurons involving neurotransmitter enzymes [choline acetyltransferase (ChaT)], peptides (calcitonin generelated peptide), and neurotrophin receptors (low-affinity receptor p75), matching those observed after axotomy (17). This damage is accompanied by axonal pathology (18) and a dramatic drop in nerve growth factor (NGF) content in the spinal cord (19,20), which recovers after therapies, which also induce a rise in NGF content (18).…”
mentioning
confidence: 91%
“…However, it is unknown whether the same observations are applicable to remyelination after injury. Moreover, treatment with recombinant human NGF inhibits the development of inflammation and demyelination in the nonhuman primate model of EAE (54), and a better remyelination is obtained by treatment that restores NGF content to control values in chronic EAE in rat, where NGF levels are dramatically lower (18,20).…”
Section: Cns Inflammation and The Cholinergic System Of The Basal Formentioning
confidence: 99%